2020
DOI: 10.1177/1120672119874598
|View full text |Cite
|
Sign up to set email alerts
|

One-year outcomes of the Polish treatment program for the wet form of age-related macular degeneration using intravitreal therapy

Abstract: Purpose: To report 12-month outcomes of a Polish National Treatment Program using aflibercept and ranibizumab in eyes with wet, age-related macular degeneration in routine clinical practice. Material and Methods: This was a non-randomized, retrospective, observational multicenter study. Anonymous data contained in the electronic Therapeutic Program Monitoring System were utilized in this study. Results: The study population consisted of 2828 eyes from 2718 patients. The median age was 76.0 [70.0, 81.0] years; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
(38 reference statements)
1
9
0
Order By: Relevance
“…Till November 2015 (our study was concluded in September 2015) treatment of patients with wet AMD has been an epidemiological and economical problem in Poland. Since that date special treatment program financed from public funds started and the situation slowly improved (Figurska et al, 2020). Mekjavic et al have provided a comprehensive overview of the clinical and economic burden of wet-AMD and DME in Central and Eastern Europe and the status quo associated with their management (Jaki Mekjavic et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Till November 2015 (our study was concluded in September 2015) treatment of patients with wet AMD has been an epidemiological and economical problem in Poland. Since that date special treatment program financed from public funds started and the situation slowly improved (Figurska et al, 2020). Mekjavic et al have provided a comprehensive overview of the clinical and economic burden of wet-AMD and DME in Central and Eastern Europe and the status quo associated with their management (Jaki Mekjavic et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these eyes might receive less injections. According to recommendations of the drug program [ 6 ]. ranibizumab was administered in PRN scheme.…”
Section: Discussionmentioning
confidence: 99%
“…Anonymous data were collected from the drug program dedicated electronic database. Therapeutic Program Monitoring System (TPMS) is central database, supervised by NHF utilized to monitor execution of the therapeutic program [ 6 ]. TPMS records from December 2015 to December 2020 were analyzed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations